Clinicopathologic Characteristics of Patients with Gastric Superficial Neoplasia and Risk Factors for Multiple Lesions after Endoscopic Submucosal Dissection in a Western Country - Brito-Gonçalves,Gisela (2020)
Background: Endoscopic submucosal dissection (ESD) is a treatment for early gastric neoplasms that preserves the stomach. However, the risk of multiple lesions persists. Objectives: To assess clinicopathologic characteristics of patients with early gastric neoplasms in a Western country and evaluate risk factors for multiple gastric lesions, synchronous, or metachronous. Methods: A retrospective cohort of 230 consecutive patients who underwent ESD for primary neoplasms from 2012 to 2017 (median follow-up: 33 months) was assessed to determine the clinicopathologic characteristics and risk factors for multiple lesions. Results: The mean age was 68 years, and 53.9% were male. Current/former smoking status was present in 40.4%, and 29.5% had family history of gastric cancer. A third of the patients had only focal gastric atrophy/metaplasia (operative link on gastritis assessment/operative link on gastric intestinal metaplasia assessment [OLGA/OLGIM] I/II; endoscopic grading of gastric intestinal metaplasia [EGGIM] 1-4). Synchronous and metachronous lesions occurred in 14.3 and 8.6% of patients, respectively. There was a trend for higher risk of multiple lesions in smokers and patients with extensive metaplasia (EGGIM > 4), but only older age was an independent risk factor (OR 3.30; 95% CI 1.05-10.34). Age > 60 years (OR 10.10, 95% CI 1.40-88.04), current/former smoking status (OR 3.64, 95% CI 1.07-12.40), and OLGIM III/IV (OR 3.07, 95% CI 1.01-9.36) were independent risk factors for synchronous lesions. No risk factors for metachronous lesions were found. Conclusions: Surveillance limited to patients with advanced stages of gastritis may miss some primary superficial neoplasms. Although older age increases the risk of multiple lesions, no risk factors were found for metachronous lesions. Therefore, endoscopic surveillance after ESD should be done equally in all patients.